Synthesis and functionalization of chitosan built hydrogel with induced hydrophilicity for extended release of sparingly soluble drugs. Issue 4 (4th March 2018) - Ullah, Faheem; Javed, Fatima; Othman, M. B. H.; Khan, Abbas; Gul, Rukhsana; Ahmad, Zulkifli; Md. Akil1, Hazizan
Abstract: Addressing the functional biomaterials as next-generation therapeutics, chitosan and alginic acid were copolymerized in the form of chemically crosslinked interpenetrating networks (IPNs). The native hydrogel was functionalized via carbodiimide (EDC), catalyzed coupling of soft ligand (1, 2-Ethylenediamine) and hard ligand (4-aminophenol) to replace –OH groups in alginic acid units for extended hydrogel- interfaces with the aqueous and sparingly soluble drug solutions. The chemical structure, Lower solution critical temperature (LCST ≈ 37.88 °C), particle size ( Z h, app ≈ 150–200 nm), grain size (160–360 nm), surface roughness (85–250 nm), conductivity (37–74 mv) and zeta potential (16–32 mv) of native and functionalized hydrogel were investigated by using FT-IR, solid state- 13 C-NMR, TGA, DSC, FESEM, AFM and dynamic light scattering (DLS) measurements. The effective swelling, drug loading (47–78%) and drug release (53–86%) profiles were adjusted based on selective functionalization of hydrophobic IPNs due to electrostatic complexation and extended interactions of hydrophilic ligands with the aqueous and drug solutions. Drug release from the hydrogel matrices with diffusion coefficient n ≈ 0.7 was established by Non- Fickian diffusion mechanism. In vitro degradation trials of the hydrogel with a 20% loss of wet mass in simulated gastric fluid (SGF) and 38% loss of wet mass in simulated intestinal fluid (SIF), were investigated for 400 h through bulk erosion. Consequently, a slower rate of drug loading and release was observed for native hydrogel, due to stronger H-bonding, interlocking and entanglement within the IPNs, which was finely tuned and extended by the induced hydrophilic and functional ligands. In the light of induced hydrophilicity, such functional hydrogel could be highly attractive for extended release of sparingly soluble drugs.